Reflective Counselling Technique and Emotional Intelligence Training in Managing Expressed Performance-Anxiety of Trainee Counsellors in South-South Nigeria - Okoiye; E., O.; Anusiem, &; U., A. (British Journal of Marketing Studies, 2017)
This study investigated effects of emotional intelligence and self-efficacy training in enhancing counselling efficacy of undergraduate counselling practicum trainees in South-East Nigeria. The study adopted pre-test-post-test, control group quasi-experimental design with a 3x2x2 factorial matrix. Simple random sampling technique was used to select ninety (90) Guidance and Counselling practicum undergraduates from three tertiary institutions in South-East Nigeria. The participants were randomly assigned to groups. Participants in the two treatment groups were exposed to eight weeks of emotional intelligence and self-efficacy training. One instrument was used: The Counsellor Activity Self-Efficacy Scale (CASES) (?= 0.97). Three hypotheses were tested at 0.05 level of significance. Data were analysed using Analysis of Covariance. There was a significant main effect of treatment on counselling efficacy scores of undergraduate counselling practicum trainees F(2,58)=55.140, P<0.05. Also, there was significant main effect of age on counselling efficacy scores of undergraduate counselling practicum trainees exposed to treatments (F (1,77) = 3.651, P < .05). However, there was no significant main effect of gender on counselling efficacy scores of undergraduate counselling practicum trainees exposed to treatment (F(1,77) = 0.741, P > .05). Emotional intelligence and self-efficacy training were effective in enhancing counselling efficacy of undergraduate counselling practicum trainees. Undergraduate counselling practicum trainees should be exposed to psychological intervention programmes such as emotional intelligence and self-efficacy training that would help enhance their counselling efficacy competence and capability to effectively dispense their professional service to humanity.